Analisis Hubungan Produk Domestik Bruto dan Inflasi Terhadap Jumlah Uang Beredar di Indonesia Tahun 2015-2024 - Anggita Siregar; Irsad Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The money supply is an important indicator in maintaining monetary stability and guiding a country’s economic development. Gross domestic product (GDP) and inflation are two macroeconomic variables that are presumed to have a strong relationship with the dynamics of the money supply. This study aims to analyze the relationship between gross domestic product and inflation on the money supply in Indonesia using secondary time-series data. The analytical method employed is multiple linear regression with correlational testing. The results of the study show, first, that there is a positive and significant relationship between gross domestic product and the money supply in Indonesia. Second, there is a significant relationship between inflation and the money supply in Indonesia. Simultaneously, gross domestic product and inflation do not have a significant relationship with the money supply.